2014
DOI: 10.1111/micc.12117
|View full text |Cite
|
Sign up to set email alerts
|

Exercise‐Induced Capillary Growth in Human Skeletal Muscle and the Dynamics of VEGF

Abstract: In skeletal muscle, growth of capillaries is an important adaptation to exercise training that secures adequate diffusion capacity for oxygen and nutrients even at high-intensity exercise when increases in muscle blood flow are profound. Mechanical forces present during muscle activity, such as shear stress and passive stretch, lead to cellular signaling, enhanced expression of angiogenic factors, and initiation of capillary growth. The most central angiogenic factor in skeletal muscle capillary growth is VEGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
140
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(146 citation statements)
references
References 142 publications
3
140
1
2
Order By: Relevance
“…VEGF is dominantly secreted by working skeletal muscles, an essential factor to increase capillary density, oxygen delivery and thereby exercise performance (109)(110)(111). Based on our previous results showing improved muscular exercise capacity after HIT (30), and now the finding of an increased VEGF response, we suggest that this mechanism is of high importance also in the HTx recipients.…”
Section: Hit and The Immediate Responses In Markers Of Inflammation Amentioning
confidence: 79%
“…VEGF is dominantly secreted by working skeletal muscles, an essential factor to increase capillary density, oxygen delivery and thereby exercise performance (109)(110)(111). Based on our previous results showing improved muscular exercise capacity after HIT (30), and now the finding of an increased VEGF response, we suggest that this mechanism is of high importance also in the HTx recipients.…”
Section: Hit and The Immediate Responses In Markers Of Inflammation Amentioning
confidence: 79%
“…VEGF is the main angiogenic factor in skeletal muscle capillary growth, and is stimulated by mechanical forces during muscle activity (shear stress and stretch) (Hoier & Hellsten, 2014). The skeletal muscle fibers contain large stores of VEGF within vesicles, and during exercise, these vesicles are secreted into the extracellular fluid (Hoier & Hellsten, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…They showed that eight weeks of moderate intensity cycle training in sedentary healthy young males, lead to an approximate 40% increase in capillary density in the thigh muscle (8). In general, the literature shows that, when previously sedentary, healthy individuals are subjected to periods of 4 to 8 weeks of endurance training of moderate intensities at between 60% and 80% of VO 2max , an increase in capillarization of between 10% and 40% is observed (190,206,232) (Fig. 8).…”
Section: Effect Of Endurance Training On Capillary Growthmentioning
confidence: 94%